2006
DOI: 10.1158/1541-7786.mcr-06-0110
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin 2 Antagonizes the Proangiogenic Action of Ras in Transformed Cells

Abstract: Lipocalin 2 is an iron-binding secreted protein that converts embryonic kidney mesenchyme to epithelia. Previously, we reported that lipocalin 2 could revert 4T1-ras-transformed mesenchymal tumor cells to a more epithelial phenotype, increase E-cadherin expression, and suppress cell invasiveness in vitro and in vivo, indicating that lipocalin 2 is a metastasis suppressor. Here, we show that lipocalin 2 can suppress the ras-induced expression of vascular endothelial growth factor in 4T1 cells via down-regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 53 publications
1
30
1
Order By: Relevance
“…2 In malignant RAS-transformed cells, Lipocalin-2 induced an epithelial phenotype, blocking their capacity for growth, invasiveness, and metastasization. 11,25 In our study, Sw620 and Hct116 cells that included the K-ras mutations were sensitive to ZD55-Lipocalin-2, especially Sw620 cells in vivo. As such, ZD55-Lipocalin-2 may be a promising agent for treating colorectal cancer that is resistant to chemotherapy.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…2 In malignant RAS-transformed cells, Lipocalin-2 induced an epithelial phenotype, blocking their capacity for growth, invasiveness, and metastasization. 11,25 In our study, Sw620 and Hct116 cells that included the K-ras mutations were sensitive to ZD55-Lipocalin-2, especially Sw620 cells in vivo. As such, ZD55-Lipocalin-2 may be a promising agent for treating colorectal cancer that is resistant to chemotherapy.…”
Section: Discussionmentioning
confidence: 51%
“…Some studies have demonstrated that Lipocalin-2 has antitumor and antimetastatic effects in some neoplasias, such as cancer from the colon, ovary, and pancreas, due to its inhibition of the proneoplastic protein hypoxia-inducible factor 1, FA-Kinase phosphorylation, and vascular endothelial growth factor (VEGF) synthesis. [8][9][10][11][12] Apoptosis induced by Lipocalin-2 in cells was also reported, 13,14 but not in colorectal cancer cells. Moreover, there is no direct evidence showing therapeutic effects of Lipocalin-2 in colorectal cancer.…”
Section: Introductionmentioning
confidence: 77%
“…Some of the anticancer properties of NGAL are due to its ability to inhibit the expression of hypoxia inducible factor-1a (HIF-1a) dependent synthesis of vascular endothelial growth factor (VEGF) [104]. Also NGAL can inhibit and phosphorylation of focal adhesion kinase (FAK) and…”
Section: Effects Of Ngal On Cancer Progressionmentioning
confidence: 99%
“…Markedly induced genes common to all three arrays included Lcn2 (lipocalin 2) and MT2 (metallothionein 2), which are multifunctional iron-binding proteins. [23][24][25] Highly downregulated transcripts shared by each include Clec4f (C-type lectin domain family 4, member F) and Tm9sf2 (transmembrane 9 superfamily member 2), which are poorly characterized genes putatively involved in carbohydrate binding and endosome function, respectively. 26,27 Notably, a number of highly regulated genes were differentially affected by the D-type cyclins.…”
Section: Induction Of Hepatocyte Proliferation By the D-type Cyclinsmentioning
confidence: 99%